1990
DOI: 10.1210/jcem-70-1-192
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adrenal Autonomy in Cushing's Syndrome: A Comparison betweenin Vivoandin VitroResponsiveness of the Adrenal Gland

Abstract: We measured cortisol and precursor steroid production in response to ACTH, cholera toxin, and forskolin by the dispersed adrenocortical cells prepared from the adrenal glands of 10 patients with different forms of Cushing's syndrome. The cells prepared from the hyperplastic adrenal glands from 4 patients with Cushing's disease responded in a dose-dependent manner to ACTH, cholera toxin, and forskolin. The adrenal cells prepared from 4 encapsulated adrenal adenomas showed no (n = 2), a lowered (n = 1), or a cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…The observation that the increase in the cortisol level due to ACTH in patient B could indicate that ACTH-R expressed in the adenoma is functional. This assumption was supported by the findings of Lamberts et al [23] and Mizuno et al [24]. They showed that ACTH stimulated cortisol secretion by isolated adenoma cells from some patients with Cushing's syndrome.…”
Section: Resultssupporting
confidence: 61%
“…The observation that the increase in the cortisol level due to ACTH in patient B could indicate that ACTH-R expressed in the adenoma is functional. This assumption was supported by the findings of Lamberts et al [23] and Mizuno et al [24]. They showed that ACTH stimulated cortisol secretion by isolated adenoma cells from some patients with Cushing's syndrome.…”
Section: Resultssupporting
confidence: 61%
“…They may be relatively or absolutely deficient in one or more enzymes, including 3/?-hydroxysteroid dehydrogenase/A5-A4 isomerase, 21-hydroxylase or 11/3-hydroxylase (2,4,20,21). Aberrant steroidogenesis is characteristic of carcinomas that often secrete a greater amount of precursor steroids than either normal adrenals or benign adenomas.…”
Section: Steroid Production In Adrenocortical Tumoursmentioning
confidence: 99%
“…The mechanism(s) underlying autonomous steroidogenesis is unknown, fn addition, some tumours, mainly carcinomas, become insensitive to the action of ACTH. Various in vitro studies (21)(22)(23)(24) suggest that this defect is due to one of several biochemical abnormalities, such as a defect of the ACTH receptor-adenylyl cyclase complex (22,23) or a defect of the c-AMP-dependent protein kinase (22)(23)(24).…”
Section: Steroid Production In Adrenocortical Tumoursmentioning
confidence: 99%
“…Yet about half of the adenomas respond in vivo to exogenous ACTH; the other half and most carcinomas do not (Bertagna & Orth, 1981). The molecular defect responsible for this lack of responsiveness is unknown; functional studies in vitro merely indicate that it is different in different tumours, and may be at the receptor or post-receptor level (Riou et al, 1977;Sharma et al, 1977;Lamberts et al, 1990).…”
mentioning
confidence: 99%